2014
DOI: 10.1186/1471-2458-14-527
|View full text |Cite
|
Sign up to set email alerts
|

Population correlates of circulating mercury levels in Korean adults: the Korea National Health and Nutrition Examination Survey IV

Abstract: BackgroundPrior studies focused on bioaccumulation of mercury (Hg) and on large, long-lived fish species as the major environmental source of Hg, but little is known about consumption of small-sized fish or about non-dietary determinants of circulating Hg levels. The purpose of this study was to evaluate whole blood mercury concentration (WBHg) and its major dietary and non-dietary correlates in Korean adults.MethodsWe analyzed cross-sectional data from 3,972 (male = 1,994; female = 1,978) participants who com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
3
17
1
Order By: Relevance
“…It should be underlined that the correlation between the mercury content of bones and the body mass index (BMI) was not recognized in previous studies. Cho et al (2014) found positive associations between the BMI and the whole blood Hg levels. In turn, in the Korean study, mercury concentrations in the blood were significantly higher in males than in females.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be underlined that the correlation between the mercury content of bones and the body mass index (BMI) was not recognized in previous studies. Cho et al (2014) found positive associations between the BMI and the whole blood Hg levels. In turn, in the Korean study, mercury concentrations in the blood were significantly higher in males than in females.…”
Section: Discussionmentioning
confidence: 98%
“…In the Polish study by Michalak et al (2014), the Hg content of hair positively correlated with BMI. The mechanisms of the relationship between mercury content and body weight are not fully understood (Cho et al 2014). One of the hypotheses is connected with the influence of the endocrine system (mainly estrogen) on fat tissue and bones (Dermience et al 2015), which may indirectly confirm the finding that concentrations of Hg in the cortical bone in patients without osteoporosis were about 60 % higher than in patients with osteoporosis (Lanocha et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of study participants were residents in urban and rural southeastern areas (the Yeungnam area) in South Korea. Residents of the Yeungnam area have the highest blood mercury concentrations compared to those in other regions of South Korea [ 41 ], and they habitually consume whale and shark meat, which were revealed as independent correlates of toenail mercury concentration in this study. However, variations in fish and seafood consumption were not associated with the toenail mercury concentration of the study participants.…”
Section: Discussionmentioning
confidence: 61%
“…Although total fish intake was not a significant predictor of toenail mercury levels in the participants of this study, it is well known that higher fish consumption leads to accumulation of methylmercury in the human body. Participants in this study mainly resided in the Yeungnam area, where the residents have higher blood mercury levels than those residing in other regions of Korea because of traditional regional dietary culture (habitual consumption of shark and whale meat) [ 41 ]. Thus, when we included both variables of shark/whale meat and total fish intakes in the regression model simultaneously, variability in toenail mercury levels, as shown by the R 2 value, may be explained by the greater shark/whale meat intake relative to the total fish intake.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide population surveys conducted in the U.S. reported that the average daily seafood (fish and shellfish) intake was about 22.6 g [6]. Compared with Western populations, Asian populations have a higher mean daily consumption of seafood, e.g., 41.1 g among Koreans [7] and 56e97 g among the Japanese [8]. In addition, findings from studies conducted in the U.S. and Europe support the specific dietary recommendation that twice-weekly consumption of fish (about 60 g/d) is associated with a reduced risk of coronary heart disease [9,10].…”
Section: Introductionmentioning
confidence: 98%